Valence band structure of ultrathin silicon and germanium channels in metal-oxide-semiconductor field-effect transistors - Low, Tony (2013)
The ultrathin body (UTB) silicon-on-insulator metal-oxide-semiconductor field-effect transistor MOSFET is promising for sub-50-nm complementary metal-oxide semiconductor technologies. To explore a high-mobility channel for this technology, this paper presents an examination of Si and Ge hole sub-band structure in UTB MOSFETs under different surface orientations. The dependence of the hole subband structure on the film thickness (TBody) was also studied in this work. We found that the valence-band mixing in the vicinity of the zone center is strongly dependent on TBody for both Si and Ge, particularly for the <110> surface orientation. This gives rise to the following two phenomena that crucially affect the electrical characteristics of p-MOSFETs: (1) an anomalous increase of quantization mass for <110> Si and Ge surfaces as TBody is scaled below 5 nm. (2) The dependence of energy dispersion and anisotropy on TBody especially for the <110> surface, which advantageously increases hole velocity along the [011] channel as TBody is decreased. The density of states for different surface orientations are also calculated, and show that—for any given surface orientation—Ge has a smaller density of states than Si. The Ge <110> surface has the lowest density of states among the surface orientations considered.